The Challenges of Youth Empowerment through Access to Credit in the Rural Areas of Nigeria - Aliero, Haruna Mohammed; Ibrahim, Saifullahi Sani (European Journal of Sustainable Development, 2013)
Unemployment and poverty are endemic among Nigerian youth in spite of numerousapproaches to curtail the menace Access to credit is critical to enable the poor totransform their production systems and thus exit poverty. It is a well known fact that anefficient financial sector that responds to the needs of the private sector increasesinvestment, enhances economic growth, and creates job opportunities which is one of themajor challenges for developing economies. This paper examines the role of creditdeepening on youth empowerment and poverty reduction in Nigeria. The approach of thepaper is qualitative and uses content analysis; literature was reviewed and thereafterconclusion was drawn based on the literature weight. It is however important to note thateconomic empowerment through accessibility to credit could be achieved if and only iffactors like collateral, interest rate, transaction cost and financial literacy, among othersthat pose challenges in accessing credit are remedied Specifically we recommend Indianmodel (Bharatia Yuva Shakti).